1985
DOI: 10.1159/000153545
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships between Indians and Their Neighboring Populations

Abstract: Using gene frequency data for 18 protein and blood group loci, we studied the genetic relationships of four Indian subcontinent populations (peoples from Punjab, Gujarati, Andhra Pradesh, and Bangladesh) with their neighboring populations (Iranians, Afghans, Sinhalese in Sri Lanka, Nepalese, Bhutanese, Malays, Bataks in northern Sumatra, and Chinese). The results obtained indicate that the four Indian subcontinent populations and the Sinhalese are genetically closer to Iranians and Afghans (Caucasoid) than to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A previous observation of gene frequency data for 18 protein and blood group loci suggested that Sinhalese are Ancestral alleles (111A of SLC24A5 and 374L of SLC45A2) are indicated by blue, and derived alleles (111T of SLC24A5 and 374F of SLC45A2) are indicated by red closer to Iranians and Afghans than to Mongoloids [18] and that the constitutions of the FUT2 allele of Sinhalese and Tamils are similar [21]. Thus, there is little or no genetic flow from neighboring East or Southeast Asian populations.…”
Section: Resultsmentioning
confidence: 82%
“…A previous observation of gene frequency data for 18 protein and blood group loci suggested that Sinhalese are Ancestral alleles (111A of SLC24A5 and 374L of SLC45A2) are indicated by blue, and derived alleles (111T of SLC24A5 and 374F of SLC45A2) are indicated by red closer to Iranians and Afghans than to Mongoloids [18] and that the constitutions of the FUT2 allele of Sinhalese and Tamils are similar [21]. Thus, there is little or no genetic flow from neighboring East or Southeast Asian populations.…”
Section: Resultsmentioning
confidence: 82%
“…However, studies based on human leukocyte antigen (HLA) have shown that Sinhalese are more likely to originate from the Aryans than the Dravidians [30]. Sinhalese are genetically closer to Caucasoid populations than to other neighboring Mongoloid populations [31]. The history of Sri Lanka has been based on the Mahavansa , the great chronicle of Sri Lanka, which was written by the Mahanama thero in the fifth century AD [32].…”
Section: Discussionmentioning
confidence: 99%
“…The first systematic surveys of human variation in India focused on anthropometric traits, and found that India is structured along lines of ethnicity as well as geography1, a result that has since been confirmed by blood group, protein polymorphism2,3 and genetic analysis4. Genetic studies have further documented differences in relatedness to West Eurasians5,6,7,8, while mitochondrial DNA (mtDNA) studies have shown that India harbors deep rooted lineages that share no common ancestry with groups outside of South Asia for tens of thousands of years9.…”
mentioning
confidence: 99%